Aspectos jurídicos da unificação monetária nos processos de integração regional - Ciminelli, Selma Fontes (2007)
The object of this theme is to approach the aspects related to currency, studying the paths taken through civilization up to he process of monetary unification. The methodology applied will start with the study of the origens of currency, its evolution, functions and position in both national and international financial system. We will also approach the process of regional integration, phocusing on European Union, as the pioneer experience on implementing one currency- the Euro- also discussing the interface between the unicism and the sovereign power of nations, under the light of classical theories and the evolution of the concept of sovereignity. Finally, as a reflexion over the monetary unification, we will evaluate the effects that monetary unification can cause in the international market; at the same time analyzing the risks and the advantages of an hypothetical global system of monetary unification